2022
DOI: 10.3390/ijms23031046
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Androgen Receptor Activity on Prostate-Specific Membrane Antigen Expression in Prostate Cancer Cells

Abstract: Prostate-specific membrane antigen (PSMA) is an essential molecular regulator of prostate cancer (PCa) progression coded by the FOLH1 gene. The PSMA protein has become an important factor in metastatic PCa diagnosis and radioligand therapy. However, low PSMA expression is suggested to be a resistance mechanism to PSMA-based imaging and therapy. Clinical studies revealed that androgen receptor (AR) inhibition increases PSMA expression. The mechanism has not yet been elucidated. Therefore, this study investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Presumably due to wellknown cellular and molecular differences between both cell lines, e.g. in androgen sensitivity, androgen receptor expression, and p53 status (48,49), PC-3 cells are more resistant to anticancer treatment than LNCaP cells, as suggested by literature data (50)(51)(52)(53). Additionally, one cannot exclude the possibility of varying transfection efficiencies utilizing chemically modified RNA molecules for the transfection of LNCaP and PC-3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Presumably due to wellknown cellular and molecular differences between both cell lines, e.g. in androgen sensitivity, androgen receptor expression, and p53 status (48,49), PC-3 cells are more resistant to anticancer treatment than LNCaP cells, as suggested by literature data (50)(51)(52)(53). Additionally, one cannot exclude the possibility of varying transfection efficiencies utilizing chemically modified RNA molecules for the transfection of LNCaP and PC-3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of PSMA can be very heterogeneous [22][23][24]. Many in vitro and in vivo studies showed that PSMA expression and PSA secretion are independently regulated with different behaviour after treatment with anti-hormones [25,26]. It seems that in men with hormonesensitive cancers, androgen deprivation leads in most cases to a decrease in maximum and mean standardized uptake value (SUV) at PSMA PET/CT as well as PSA secretion.…”
Section: Discussionmentioning
confidence: 99%
“…The patient’s cohort has previously been described in Sommer et al, 2022 and the samples were selected from the Tumor and Normal Tissue Bank of the University Cancer Center Dresden ( Ebersbach et al, 2022 ; Sommer et al, 2022 ). The cohort of this study contained 116 tissue specimens of 97 PCa patients undergoing transurethral resection of the prostate (TURP) recruited from 2011 to 2020.…”
Section: Methodsmentioning
confidence: 99%